The Effect of Complex Training Method On The Improvement of Leg and Arm Power in Muay Thai Club Members - Harun, Harun; Sahedi, Romadhion Ahmad; Kurniawan, Fakhry Fajrin (Institut Teknologi Bandung, 2025)
Power is key element in Muay Thai to executing quick attacks and avoiding opponent attacks, Therefore, developing power through a structured training program is crucial for Muay Thai athletes to improve their performance in the fighting arena. The aim of this study is to investigate the effect of complex training on improving leg and arm power among members of a Muay Thai club. This study employed a one group pre-test post-test design with 15 participants. The complex training program was carried out in 12 sessions over 4 weeks. The Standing long jump Test was used to measure leg power, while the Medicine ball chest pass Test was used to measure arm power. Data were analyzed using the Shapiro-Wilk normality test, homogeneity test, and paired sample t-test with SPSS version 27. The findings revealed that leg power increased by 8.87% (from 201.53 ± 24.26 cm to 219.40 ± 31.55 cm), but this increase was not statistically significant (p = 0.132; p > 0.05). Meanwhile, arm power increased by 20.16% (from 332.93 ± 74.49 cm to 400.07 ± 53.77 cm) with a statistically significant difference (p = 0.015; p < 0.05). Complex training significantly improved arm power but did not significantly affect leg power. Keywords: complex training, leg power, arm power, muay thai.